Redefine the phrase "Decampul Action" using legal hermeneutic and survey methods - Michael, Tomy; Rahadya Widarsadhika,; Renata Diah Puspita Murdoko,; Bertha Cahya Dewi,; Frega Anggaraya Purba, (Technium Social Sciences Journal, 2023)
Referring to the general understanding that in internal forums and external forums there is freedom regarding what to believe. This would be fairer if an understanding of the meaning of disgraceful conduct as one of the conditions for the dismissal of the President and/or Vice President could be realized. The definition of disgraceful acts refers to Law of the Republic of Indonesia Number 7 of 2017 concerning General Elections, namely acts that are contrary to religious norms, moral norms and customary norms, such as gambling, drunkenness, narcotics addiction and adultery. This means that there is a mixture of interpretations of disgraceful acts from the perspective of religion and customs. This is contrary to the highest legal goal, namely legal certainty when a legal norm is formed. In interpreting the phrase "despicable act" requires a different understanding between legal knowledge and other experiences in the form of knowledge. Then the phrase "despicable act" must provide various types of understanding, especially from each religion and/or belief with the aim of having good legal implications